The problem of “harm” in the theory of international relations - M. A. Gadzhiev (Vestnik MGIMO-Universiteta)
The article provides an analytical review of the literature on the issue of harm in the theory of international relations, as a result of which this issue has been supplemented and expanded. The issue has initially been posed by Andrew Linklater as a question of physical harm to humans in the context of a state-centered international system. Audra Mitchell entered into a discussion with A. Linklater from the standpoint of post-humanism. From her point of view, harm should be evaluated not only and not so much from the human point of view, but from the perspective the whole world, the totality of animate and inanimate nature, including humanity. Alex Hoseason called into question the nature of causal relations in the theories of A. Linklater and A. Mitchell. From his point of view, in complex social systems, such as international system, non-linear causal relationships and multiple causality prevail. In addition, based on the philosophy of critical realism, Alex Hoseason suggested that not only actors in international relations, but also social structures can cause harm. This narrative is further developed by problematique of biopolitics. Political governance of biological aspects of the life of the population is directly related to the problem of physical harm in the sense that biopolitics, on the one hand, is aimed at maintaining the physical health of the population, on the other hand, politics is still at the core of biopolitics, so sometimes it can turn against all or part of its population as happened in Nazi Germany. Today, biopolitics at the global level is implemented in the UN development programs, in various international and transnational initiatives to promote international development, as well as in global health governance. Expanding the problematique of harm to biopolitics brings us back to the original anthropocentric model of harm proposed by A. Linklater, nevertheless, this step allows us to analyze not only the causes of harm, but also approaches to reducing it.